Herbal therapy in Covid-19: A systematic review of medicinal plants effective against Covid-19 - Heru Widoyo; Zahraa Yassen Mohammed; Andrés Alexis Ramírez-Coronel; Acim Heri Iswanto; Usman Thattarauthodiyil; Ameer S. Alkhayyat; Mohammad Karimi; Mahmoud Bahmani; Zohre Eftekhari (Caspian Journal of Environmental Sciences)
In 2019, a new disease called Covid-19 was detected in Wuhan located in China which caused seriously disease or death at any age. This disease has various symptoms such as fever, chills, cough, sore throat, headache, body pain, muscle pain, diarrhoea, and vomiting. In this review study, articles related to the subject were searched using scientific sites such as Medline, PubMed, and Google Scholar using the keywords of traditional medicine, medicinal plants, and Covid-19. After downloading the articles, irrelevant articles were removed and related articles were reviewed. According to the results obtained from the review of the literature, the effective medicinal herbs including Zingiber officinale, Alpinia officinarum, Cinnamomum zeylanicum, Nigllea sativa, Citrus paradise, Laurus nobilis L. and Echinacea purpura were the most important medicinal herbs used in treatment of Coronavirus. Antiviral chemical drugs usually inhibit the virus by disrupting the key protein and viral virulence factors. Probably, medicinal plants inhibit corona virus with a mechanism similar to the chemical drugs. Therefore, it is possible to produce effective herbal medicines as alternative for synthetic drugs and reduce the pain and suffering from Covid-19 in patients.